The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fendo.2021.660095
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Fission Protein 1: Emerging Roles in Organellar Form and Function in Health and Disease

Abstract: Mitochondrial fission protein 1 (Fis1) was identified in yeast as being essential for mitochondrial division or fission and subsequently determined to mediate human mitochondrial and peroxisomal fission. Yet, its exact functions in humans, especially in regard to mitochondrial fission, remains an enigma as genetic deletion of Fis1 elongates mitochondria in some cell types, but not others. Fis1 has also been identified as an important component of apoptotic and mitophagic pathways suggesting the protein may hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 417 publications
(648 reference statements)
1
49
0
Order By: Relevance
“…Coherently, MFF has been shown to be essential for this oligomerization inhibition at peroxisomes, but not at mitochondria. The involvement of peroxisome specific proteins, such as PEX11 ( Visser et al, 2007 ; Carmichael and Schrader, 2022 ), and other fission machinery proteins, such as FIS1 ( Ihenacho et al, 2021 ), on the vMIA-dependent evasion of antiviral signalling should be adressed in the future, in order to further unravel de mechanisms involved and explain the observed differences between the processes occuring at peroxisomes and mitochondria. Based on all our results, we suggest a model for vMIA’s mechanism of action towards peroxisomes, which is depicted in Figure 6 : upon infection, vMIA interacts with PEX19 at the cytoplasm and travels to peroxisomes, where it interacts with MAVS.…”
Section: Discussionmentioning
confidence: 99%
“…Coherently, MFF has been shown to be essential for this oligomerization inhibition at peroxisomes, but not at mitochondria. The involvement of peroxisome specific proteins, such as PEX11 ( Visser et al, 2007 ; Carmichael and Schrader, 2022 ), and other fission machinery proteins, such as FIS1 ( Ihenacho et al, 2021 ), on the vMIA-dependent evasion of antiviral signalling should be adressed in the future, in order to further unravel de mechanisms involved and explain the observed differences between the processes occuring at peroxisomes and mitochondria. Based on all our results, we suggest a model for vMIA’s mechanism of action towards peroxisomes, which is depicted in Figure 6 : upon infection, vMIA interacts with PEX19 at the cytoplasm and travels to peroxisomes, where it interacts with MAVS.…”
Section: Discussionmentioning
confidence: 99%
“…A 15-kDa soluble domain inside this domain with two tetratricopeptide repeats (TPRs) acts as the tethering site of the mitochondrial outer membrane. The subsequent study found that FS1 recruits DRP1 from the cytosol to the fission site of mitochondria ( Ihenacho et al, 2021 ). Coimmunoprecipitation studies suggest that FIS1 may act as a downstream factor of Mff of DRP1 recruitment and assembly at scission sites ( Shen et al, 2014 ).…”
Section: Significant Players Of Mitochondrial Dynamicsmentioning
confidence: 98%
“…After the recruitment to the OMM, Drp1 undergoes GTP-dependent oligomerization forming a spiral ring with an inner diameter of 20 nm [17] (see Table 1). Fis1 Fission Adaptor protein located in the OMM [16] Mdv1 Fission Adaptor protein located in the OMM [16] Mff Fission Adaptor protein located in the OMM [16] dynamin 2 Fission Mediates membrane reorganization [18] endophilin 1 Fission Mediates membrane reorganization [18] SNX9 Fission Mediates membrane reorganization [18] Mfn1-mitofusin1; Mfn2-mitoofusin 2; Opa1-optic atrophy protein 1; Parl-presenilin-associated rhomboidlike protein; Oma1-mitochondrial metalloendopeptidase Oma1; Yme1L1-ATP-dependent zinc metalloprotease YME1 Like 1 ATPase; Afg3l1-mAAA protease complex ATPase family gene-3 yeast-like-1; Drp1dynamin-related protein 1; Fis1-mitochondrial fission protein 1; Mdv1-mitochondrial division protein 1; Mff-mitochondrial fission factor; SNX9-sorting nexin 9; OMM-outer mitochondrial membrane; IMM-inner mitochondrial membrane.…”
Section: Mitochondrial Fissionmentioning
confidence: 99%
“…However, after activation, Drp1 moves from the cytosol to mitochondria [ 15 ]. This translocation is possible due to the activity of adaptor proteins located in the OMMs, such as mitochondrial fission protein 1 (Fis1), mitochondrial division protein 1 (Mdv1), and mitochondrial fission factor (Mff) [ 16 ]. After the recruitment to the OMM, Drp1 undergoes GTP-dependent oligomerization forming a spiral ring with an inner diameter of 20 nm [ 17 ] (see Table 1 ).…”
Section: Mitochondrial Dynamicsmentioning
confidence: 99%